Has a change in established care pathways during the first wave of the COVID-19 pandemic led to an excess death rate in the fragility fracture population? A longitudinal cohort study of 1846 patients. Issue 5 (6th May 2022) - Ikram, Adeel; Norrish, Alan; Ollivere, Luke; Nightingale, Jessica; Valdes, Ana; Ollivere, Benjamin J
Abstract : Objective: During the first wave of the COVID-19 pandemic, changes to established care pathways and discharge thresholds for patients with fragility fractures were made. This was to increase hospital bed capacity and minimise the inpatient risk of contracting COVID-19. This study aims to identify the excess death rate in this population during the first wave of the pandemic. Design: A longitudinal cohort study of patients with fragility fractures identified by specific International Classification of Diseases (ICD)-10 codes. The first wave of the pandemic was defined as the 3-month period between 1 March and 1 June 2020. The control group presented between 1 March and 1 June 2019. Setting: Two acute National Health Service hospitals within the East Midlands region of England. Participants: 1846 patients with fragility fractures over the aforementioned two specified matched time points. Primary and secondary outcome measures: Four-month mortality of all patients with fragility fractures with a subanalysis of patients with fragility hip fractures. Results: 832 patients with fragility fracture were admitted during the pandemic period (104 diagnosed with COVID-19). 1014 patients presented with fragility fractures in the control group. Mortality in patients with fragility fracture without COVID-19 was significantly higher among pandemic period admissions (14.7%) than the pre-pandemic cohort (10.2%) (HR=1.86; 95% CI 1.41 to 2.45; p<0.001) adjusted for age and sex. Length of stay was shorter during the pandemic period (effect size=−4.2 days; 95% CI −5.8 to –3.1, p<0.001). Subanalysis of patients with fragility hip fracture revealed a mortality of 8.4% in the pre-pandemic cohort, and 15.48% during pandemic admissions with no COVID-19 diagnosis (HR=2.08; 95% CI 1.11 to 3.90; p=0.021). Conclusions: There is a significant increase in excess death, not explained by confirmed COVID-19 infections. Altered care pathways and aggressive discharge criteria during the pandemic are likely responsible for the increase in excess deaths.